Konflikty zbrojne a prawa kobiet w świetle praktyki Komitetu ONZ ds. Likwidacji Dyskryminacji Kobiet - Sękowska-Kozłowska, Katarzyna (Przegląd Strategiczny, 2013)
Presented paper aims to answer the question what are obligations imposed on states by the UN Convention on the Elimination of All Forms of Discrimination againstWomen (1979) in relation to protection of women’s rights during the armed conflicts and peace process. Presented research is based on analysis of the practice of the UN Committee on the Elimination of Discrimination against Women, an independent control body established by the Convention to monitor implementation of its provisions by the state parties. The analysis of the Committee’s output is proceeded by the review of its control tools in order to assess their usefulness in process of verification how the states perform duties imposed on them by the Convention in such specific situation as armed conflict. The core part of presented research is based on analysis of decisions of this body, particularly the general recommendations and concluding observations addressed to the state parties.